Legal Regulation of Preimplantation Genetic Diagnosis: A Comparative Analysis of the Baltic Sea Region and the Nordic Countries - Grubliauskienė, Nastė (Teisė, 2022)
This paper examines the concept and regulation of some of the latest research in the field of fertility – preimplantation genetic diagnosis – in Lithuania, Poland, the Baltic States, and the Nordic countries. Preimplantation genetic diagnosis raises many legal and ethical questions regarding the protection of embryos, manipulation of the human genome, selection by sex, and the relation of this diagnosis to other similar studies. International legislation or guidelines define genetic testing, including pre-implantation genetic diagnosis, quite broadly, due to the scope of regulation and nuances, leaving the right to decide to the discretion of each state. National regulation of preimplantation genetic diagnosis should be specific, clearly defining cases in which preimplantation genetic diagnosis is applied.